Apology Strategy in Senior High School Students of North Aceh Dialect - Isda Pramuniati; Mahriyuni; Marice (Universitas Pendidikan Ganesha, 2023)
An apology is an important expression of contact. The form of apology differs from the form of apology in different languages, circumstances, beliefs, ethnography, and so on. In certain situations, forgiveness is a form of accepting mistakes someone makes. This study examines the apology strategies used in the North Aceh dialect among high school students. This research is qualitative research with survey analysis. The subjects of this study were 40 students. The methods used to collect data are interviews, questionnaires, and surveys. The instrument used to collect data is a questionnaire. The technique used to analyze the data is descriptive qualitative analysis. Research has shown that, although direct and indirect reasons can lead to long discussions among the interlocutors, the communicative content can be observed through indirect reasons so that shared views and attitudes can be conveyed. Further analysis of the different statistics is suggested to look at the gaps in apology across ages. Further analysis of the different statistics is recommended to examine the gaps in the apology strategy of these two variables, age group, and gender.